2021
DOI: 10.7759/cureus.19449
|View full text |Cite
|
Sign up to set email alerts
|

Myopericarditis as a Manifestation of Long COVID Syndrome

Abstract: The main presentation of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is respiratory. However, there are extrapulmonary manifestations such as myocardial and pericardial injury. The term long COVID syndrome describes the persistence of symptoms in patients who have recovered from the infection. A 31-year-old man presented with mild coronavirus disease 2019 (COVID-19) symptoms for three days. Two weeks later, he developed chest pain, pericardial rub, and pericardial effusion; he underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Since the initiation of the COVID-19 pandemic, various symptoms have been characterized in the acute phase. However, according to the recent reports, symptoms may present or persist after several weeks which is described as long COVID syndrome [ 18 ]. Long COVID can appear following severe, mild or asymptomatic SARS-CoV-2 infection as a multisystem illness.…”
Section: Discussionmentioning
confidence: 99%
“…Since the initiation of the COVID-19 pandemic, various symptoms have been characterized in the acute phase. However, according to the recent reports, symptoms may present or persist after several weeks which is described as long COVID syndrome [ 18 ]. Long COVID can appear following severe, mild or asymptomatic SARS-CoV-2 infection as a multisystem illness.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the reports described the varied symptoms and attributed them to known syndromes, denoting the multi-organ dysfunction that acute COVID-19 caused even in mild non-hospitalised adult patients [ 103 ]. These published case studies reported long term respiratory complications [ 94 ] cardiac involvement [ 93 , 100 ], neurological dysfunction [ 96 ], and autoimmune dysfunction [ 97 ]. However, the symptoms of these syndromes did reflect the physical symptoms described in the cohort studies.…”
Section: Discussionmentioning
confidence: 99%
“…Only two cases of myopericarditis related to post COVID-19 syndrome in young patients has been reported [8 , 9] . Post-COVID myocarditis manifest itself in two main clinical forms: isolated arrhythmias and systolic dysfunction [10] .…”
Section: Discussionmentioning
confidence: 99%